1992
DOI: 10.3758/bf03213374
|View full text |Cite
|
Sign up to set email alerts
|

Extinction of the overshadowing CS after overshadowing in conditioned taste aversion

Abstract: Using a conditioned taste aversion preparation, overshadowing of flavor-illness association was produced through the presentation of a second flavor during the interval between the fIrst flavor and illness. The modulatory effects of extinguishing the association between the second (overshadowing) flavor and illness on conditioned responding to the target flavor was investigated.In Experiment 1, we found that, following one-trial overshadowing, extinction of the overshadowing flavor had no effect on conditioned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…It may be that the salt concentration was not high (salient) enough to be conditioned (Kalat & Rozin, 1970;Rescorla & Wagner, 1972). This account seems unlikely given the extent of the literature demonstrating conditioned taste aversion when a salt solution of 1% or less is paired with other USs such as LiCl (see, e.g., Bouton, Dunlap, & Swartzentruber, 1987;Kalat & Rozin, 1970;Schachtman, Kasprow, Meyer, Bourne, & Hart, 1992;Yamamoto, Shimura, Sako, Yasoshima, & Sakai, 1994b ). Drugs of abuse like morphine are thought to induce taste aversion through different neural mechanisms than predominantly emetic drugs such as LiCl (see, e.g., Hunt & Amit, 1987;Riley, Jacobs, & LoLordo, 1978;Swank, Schafe, & Bernstein, 1995;Yamamoto, Shimura, Sako, Yasoshima, & Sakai, 1994a).…”
Section: Discussionmentioning
confidence: 93%
“…It may be that the salt concentration was not high (salient) enough to be conditioned (Kalat & Rozin, 1970;Rescorla & Wagner, 1972). This account seems unlikely given the extent of the literature demonstrating conditioned taste aversion when a salt solution of 1% or less is paired with other USs such as LiCl (see, e.g., Bouton, Dunlap, & Swartzentruber, 1987;Kalat & Rozin, 1970;Schachtman, Kasprow, Meyer, Bourne, & Hart, 1992;Yamamoto, Shimura, Sako, Yasoshima, & Sakai, 1994b ). Drugs of abuse like morphine are thought to induce taste aversion through different neural mechanisms than predominantly emetic drugs such as LiCl (see, e.g., Hunt & Amit, 1987;Riley, Jacobs, & LoLordo, 1978;Swank, Schafe, & Bernstein, 1995;Yamamoto, Shimura, Sako, Yasoshima, & Sakai, 1994a).…”
Section: Discussionmentioning
confidence: 93%
“…We addressed this problem by first examining the interaction of the overshadowing treatment and long CS duration with the intent of illuminating sources of previous discrepant reports concerning posttraining extinction of an overshadowing cue. Prior reports in the literature have often reported increases in responding to the overshadowed target after extinguishing the overshadowing cue (retrospective revaluation; e.g., Kaufman & Bolles, 1981; Matzel et al, 1985; Matzel et al, 1987), but some studies reported the opposite (mediated extinction; e.g., Schachtman et al, 1992; Shevill & Hall, 2004; Exp 1c), and other studies have found no effect (Holland, 1999; Revusky, Parker, & Coombes, 1977). Experiment 1 found that, with elemental training, conditioned suppression to the target stimulus decreased as the duration of the CS increased, and that, with compound cue training, the opposite pattern of responding was observed.…”
Section: Discussionmentioning
confidence: 96%
“…In other words, they observed mediated extinction with long duration cues. A further instance of mediated extinction within a taste aversion preparation was reported by Schachtman, Kasprow, Meyer, Bourne, and Hart (1992). They administered two flavors followed by LiCl injection, and observed overshadowing.…”
mentioning
confidence: 82%
“…Research using rats in a conditioned flavour aversion paradigm has demonstrated that short duration CSs result in weak odours being overshadowed by salient tastes but potentiate odours with long CS durations and that post-training extinction of the salient taste following long CS durations results in mediated extinction (Westbrook, Homewood, Horn, & Clarke, 1983). Crucially, following simultaneous, rather than serial, CS presentation, post-training extinction following an overshadowing preparation has been shown to result in mediated extinction (Schachtman, Kasprow, Meyer, Bourne, & Hart, 1992;Shevill & Hall, 2004),…”
Section: Methodsmentioning
confidence: 99%